ASSESSMENT OF QUALITY OF LIFE AND COGNITIVE FUNCTIONS IN PATIENTS WITH STATUS EPILEPTICISM - Umidjon J. Khodjimatov ,; Rano B. Azizova , (Central Asian Journal of Medicine, 2025)
Epilepsy remains a significant issue not only in neurology but also in medicine as a whole. The prevalence of epilepsy continues to rise among children and adults worldwide. According to the International League Against Epilepsy (ILAE), epilepsy is a brain disorder characterized by a persistent predisposition to epileptic seizures, leading to neurobiological, cognitive, psychological, and social consequences. This study aims to assess the quality of life and cognitive functions in patients with status epilepticus. A prospective, comparative, and controlled study was conducted at Andijan State Medical Institute. The study included 77 patients, divided into three groups: the main group (33 patients with status epilepticus), a comparison group (20 patients with epilepsy), and a control group (24 patients without epilepsy). The cognitive function assessment was performed using the Montreal Cognitive Assessment (MoCA) scale and a five-point rating system. The results showed that patients with status epilepticus had a higher prevalence of cognitive impairment, including mild dementia. Quality of life was also lower in these patients compared to the control and comparison groups. The findings emphasize the importance of comprehensive cognitive and quality-of-life assessments in managing epilepsy patients.